2017
DOI: 10.1007/s00425-017-2666-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and metabolic profile of Salvia officinalis populations: implications for advanced breeding strategies

Abstract: As a result of this work, we were able to characterize seven indigenous to Greece Salvia officinalis populations using genetic and metabolomic tools. These tools can be used to select the most promising genotypes, capable to design future breeding programs for high valuable varieties. An initial investigation was carried out to compare the genetic and metabolic diversity in S. officinalis grown in Greece and to discern the relationship between the two sets of data. Analysis of inter-simple sequence repeats (IS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…Depending on cultivation conditions, the most similar profiles were Iraq/Germany and Iraq/Iran. The discrepancy between metabolic and genetic similarity is in line with the results of previous studies in other plant species [34,35,68]. In contrast, chemical profiles and microsatellite markers in Citrus aurantium were correlated [69].…”
Section: Metabolic Diversity Of Hairy Root Exudates and Genetic Diversupporting
confidence: 85%
See 2 more Smart Citations
“…Depending on cultivation conditions, the most similar profiles were Iraq/Germany and Iraq/Iran. The discrepancy between metabolic and genetic similarity is in line with the results of previous studies in other plant species [34,35,68]. In contrast, chemical profiles and microsatellite markers in Citrus aurantium were correlated [69].…”
Section: Metabolic Diversity Of Hairy Root Exudates and Genetic Diversupporting
confidence: 85%
“…One of the goals of studies of chemical diversity in plants is to assess the relationship between metabolic and genetic diversity. The results of a limited number of studies indicated that patterns of genetic and metabolic similarity may be incongruent [34,35,68]. The bioreactor designed in this work will facilitate comparison of root exudates and/or hairy root exudates for plant accessions with known genetic relationships.…”
Section: Metabolic Diversity Of Hairy Root Exudates and Genetic Divermentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, the maceration of thyme provided the lupin oil with these two cyclic terpenes (1.90 ± 0.28% and 0.04 ± 0.01%, respectively). Previous studies showed that camphor and borneol are major compounds of sage essential oil . Both terpenoids were identified in sage flavored oil (9.16 ± 0.49% and 0.30 ± 0.04%, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Both terpenoids were identified in sage flavored oil (9.16 ± 0.49% and 0.30 ± 0.04%, respectively). Oxygenated terpenes from sage, such as α‐thujone, β‐thujone, bornyl acetate, have strong odor activity and might have provided the lupin oil with sage flavor.…”
Section: Resultsmentioning
confidence: 99%